Analisis Internal dan Eksternal serta Pengembangan Produk Baru: Konsep Produk, Pemasaran, dan Pendekatan Terintegrasi - Nurjaman, Ujang; Widiyana, Ende; Hidayat, Ahmad Saeful; Hafid, Abdul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
This study focuses on the internal and external analysis and the concept of new product development for a business. The main objective is to identify internal strengths and weaknesses, external opportunities and threats, and create a competitive new product strategy. Internal analysis evaluates the company's resources and capabilities, while external analysis examines market conditions, competition, and trends. SWOT and PESTEL frameworks are utilized for comprehensive assessment. Based on these analyses, the study proposes several new product ideas aimed at meeting market demands and improving competitiveness. The development process includes identifying market needs, generating and testing product concepts, and launching and evaluating the product. The findings highlight the importance of integrating internal and external factors and emphasizing customer-centric approaches to ensure successful product innovation.